Evaluation of eastern redcedar as a substrate for container-grown plant production - Starr, Zachariah William (Kansas State University, 2011)
The nursery industry in the United States, particularly in the Great Plains region is growing; however, materials used in creation of artificial substrates used to grow ornamental nursery crops continue to increase in price. Eastern Redcedar (Juniperus virginiana L.) is an indigenous plant throughout much of the United States and, in the Great Plains, it has become a pest. Use of wood-based substrates (primarily composed of pine trees) has been proven effective in both nursery and greenhouse production. Eastern Redcedar chips (JVC) could become a local and sustainable resource for the horticulture industry throughout the Midwest. Experiments were conducted to determine if JVC could be used as a substrate to replace or supplement three major substrate components; pine bark (PB), perlite, or peat moss. Four studies evaluated ornamental crop growth: two focused on comparing nursery crop production in PB and JVC, one focused on greenhouse production in peat moss, and the last on plant propagation in perlite. The first experiment (Chapter 2) involved combining ratios of JVC and PB with two fertilizer rates to grow woody plants. It was shown that while higher levels of fertilizer produced larger plants, that plants grown at either rate of fertilizer showed the same growth trends. As JVC content increased more than 20%, growth measurements such as shoot dry weight and plant height decreased. This decrease in growth can be attributed to the physical properties of JVC, which showed that as JVC content increased so did airspace with a corresponding decrease in container capacity. A follow-up experiment (Chapter 4) evaluated several different particle sizes of JVC and a PB control. It showed that despite the different particle sizes JVC substrate produced less growth than plants grown in PB though plants grown in JVC were all similar to each other. Another experiment (Chapter 3) was conducted to evaluate if JVC as a replacement for peat moss in producing greenhouse-grown annual crops. JVC’s low container capacity hindered plant growth with each increase in JVC content associated with a decrease in growth. Finally a propagation experiment (Chapter 5) used a combination of finely-ground JVC and perlite to grow cuttings of woody and herbaceous plants. It was shown that, in most cases, JVC and perlite were equivocal rooting cuttings. This work demonstrates that JVC can be used as a PB and peat moss supplement, but not a replacement nursery and greenhouse crop production. Use of JVC as a perlite replacement for plant propagation is recommended.
Keywords: Eastern redcedar; Substrate; Nursery; Greenhouse; Propagation; Hedge-apple; Horticulture (0471); Plant Sciences (0479); Soil Sciences (0481)